Comparison of body composition among Malaysian national paralympic athletes before and after the lockdown of COVID-19 - Chong, C. S. M.; Tham, C. S. (2020)
Home quarantine has resulted in lifestyle changes including restricted physical activity, poor nutritional intake and others, leading to body composition changes (Chen et al., 2020). Unfavourable body composition changes can impact athletes` physical fitness and sports performance (Bosquet et al., 2013).